The biology of deserts - Ward, David, 1961 June 15- (Oxford : Oxford University Press, 2009)
This text offers a concise but comprehensive introduction to desert ecology. As with other titles in this series, the emphasis is on the organisms that dominate this harsh environment, although pollution, conservation and experimental aspects are also considered.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Desert biology; Desert ecology